Research Notes. Distributive and Procedural Justice as Predictors of Satisfaction with Personal and Organizational Outcomes - McFarlin, Dean B.; Sweeney, Paul (Academy of Management Journal, 1992)
Distributive justice was found to be a more important predictor of two personal outcomes, pay satisfaction and job satisfaction, than procedural justice, whereas the reverse was true for two organizational outcomes-organizational commitment and subordinate?s evaluation of supervisor. However, procedural and distributive justice also interacted in predicting organizational outcomes. We discuss limitations of this study and directions for future research.